Pengaruh Buerger Allen Exercise terhadap sirkulasi ekstremitas bawah bagi penyandang diabetes melitus - Bahjatun Nadrati; Muhammad Hadi; Fitrian Rayasari (Holistik Jurnal Kesehatan, 2020)
Effectiveness of Buerger Allen Exercise on lower limb circulation among patients with diabetes mellitusBackground: Buerger Allen Exercise is a specific exercise intended to improve circulation to the feet and leg using gravitational changes to influence the distribution of body fluids to alternately help emptying and fulfilling the blood columns, and by using muscle contraction through active movement of the ankle to improve circulation of peripheral blood vessel by driving blood and blood vessel. Ankle Brachial Index (ABI) is one of the indicators to assess changes in peripheral vascularization.Purpose: To know the effectiveness of Buerger Allen Exercise on lower limb circulation among patients with diabetes mellitusMethod: A quasi-experimental by pre- and post-test with controlled group, involving 28 participants  divided by two group; interventional group and controlled group. The sampling technique is a non-probability sampling.Results: Shows by  t-test and GLM-RM  finds out that there are significant differences in the improvements of ABI average scores between interventional and controlled groups after Buerger Allen Exercise is conducted to the right leg with (p-value= 0.001; α = 0.05 ) and to the left leg with (p-value= 0.002; α = 0.05). While, GLM-RM in the research is still not able to determine the optimal point of time in practicing Buerger Allen Exercise.Conclusion: The effectiveness of Buerger Allen Exercise on lower limb circulation and suggestion that Buerger Allen Exercise can be applied as one of the nurse self-intervention to improve peripheral vascularization to patients with diabetes mellitusKeywords : Buerger Allen Exercise; Lower limb circulation; patients; diabetes mellitusPendahuluan: Buerger Allen Exercise adalah latihan khusus yang ditujukan untuk meningkatkan sirkulasi ke kaki dengan menggunakan perubahan gravitasi mempengaruhi distribusi cairan dalam tubuh dengan membantu secara bergantian untuk mengosongkan dan mengisi kolom darah, dan menggunakan kontraksi otot melalui gerakan aktif dari pergelangan kaki untuk meningkatkan sirkulasi pembuluh darah perifer dengan menggerakan darah dan pembuluh darah. Ankle Brachial Index (ABI) merupakan salah satu indikator untuk menilai perubahan vaskularisasi perifer.Tujuan: Untuk mengetahui pengaruh Buerger Allen Exercise terhadap sirkulasi ekstremitas bawah  bagi penyandang diabetes melitusMetode : Menggunakan desain kuasi eksperimen pre post tes dengan kelompok kontrol, melibatkan 28 partisipan yang dibagi dalam dua kelompok; kelompok intervensi dan kelompok kontrol. Tehnik pengambilan sampel dengan non probability sampling. Penelitian ini menggunakan t-tes dan GLM-RM.Hasil : Uji t-tes didapatkan perbedaan yang signifikan rata-rata skor peningkatan ABI antara kelompok intervensi dan kontrol setelah dilakukan Buerger Allen Exercise pada kaki kanan dengan (p-value= 0,001; α = 0,05 ) dan pada kaki kiri dengan (p-value= 0,002; α = 0,05 ). Sedangkan dengan GLM-RM pada penelitian ini belum dapat menentukan titik optimum waktu pelaksanaan Buerger Allen Exercise.Simpulan: Adanya pengaruh Buerger Allen Exercise terhadap sirkulasi ekstremitas bawah  dan disarankan agar Buerger Allen Exercise dapat diterapkan sebagai salah satu intervensi mandiri perawat dalam meningkatkan vaskularisasi perifer bagi penyandang diabetes melitus